An Integrated Linearization Technique for GaAs Bipolar WCDMA Power Amplifier - Rajendran, Jagadheswaran; Hamid, Sofiyah Sal; Kunhi Mohd, Shukri Korakkottil; Abdullah, Mohd Zaid; Ramiah, Harikrishnan; Kumar, Narendra (Indian Academy of Sciences, 2018)
Here we report a novel linearization and efficiency improvement technique for heterojunction bipolar transistor (HBT)-based Wireless Code Division Multiple Access (WCDMA) power amplifier. A process solution is proposed where a tantalum nitride (TaN) layer is strapped to the HBT base metal layer that resolves the current hogging issue. This is known as the strap ballasting technique. The resistance introduced by TaN improves the linear output power without trading-off its power added efficiency. At supply voltage of 4 V, the strap ballasting methodology improves the adjacent channel leakage ratio by 4.5 dB compared to the conventional base ballasting technique at output power of 28 dBm. The corresponding improvement in power added efficiency is 4%. The maximum output power delivered by power amplifier is 36 dBm. The proposed technique can be employed in the WCDMA power amplifier to minimize the fundamental trade-off issue between linear output power and efficiency.